Internet-Based Reporting and Earnings Quality: Determinants of Financial Performance and Firm Value - Ramdani, Achmad; Susilawati, Susi; Ramdany (Universitas Pamulang, 2025)
This study aims to analyze the influence of Internet Financial Reporting (IFR) and Earnings Quality (EQ) on firm value. It also examines whether financial performance mediates these effects. This study examines infrastructure sector firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A quantitative approach with a causal research design was applied. The samples were determined using a purposive sampling technique. Data were analyzed through panel data regression, while the Sobel test was employed to validate the presence of indirect effects. The results indicate that IFR has no significant impact on financial performance, whereas EQ has a significant negative effect on financial performance. Furthermore, IFR has a significant positive effect on firm value, while EQ has a significant negative effect on firm value. Financial performance does not have a significant effect on firm value, thus failing to mediate the relationship between IFR and firm value or between EQ and firm value. These findings confirm that IFR practices can increase positive investor perceptions, but low earnings quality negatively impacts performance and market valuation.